Investigating the quaternary structure of a homomultimeric catechol 1,2-dioxygenase: An integrative structural biology study - Arisbeth Guadalupe Almeida-Juarez; Shirish Chodankar; Liliana Pardo-López; Guadalupe Zavala-Padilla; Enrique Rudiño-Piñera (PLoS ONE, 2025)
The structural analysis of catechol 1,2 dioxygenase from Stutzerimonas frequens GOM2, SfC12DO, was conducted using various structural techniques. SEC-SAXS experiments revealed that SfC12DO, after lyophilization and reconstitution processes, can form multiple enzymatically active oligomers, including dimers, tetramers, and octamers. These findings differ from previous studies, which reported active dimers in homologous counterparts with available crystallographic structures, or trimers observed exclusively in solution for SfC12DO and its homologous isoA C12DO from Acinetobacter radioresistens under low ionic strength conditions. In some cases, tetramers were also reported, such as for the Rodococcus erythropolis C12DO. The combined results of Small-Angle X-ray Scattering, Dynamic Light Scattering, and Transmission Electron Microscopy experiments provided additional insights into these active oligomers’ shape and molecular organization in an aqueous solution. These results highlight the oligomeric structural plasticity of SfC12DO, proving that it can exist in different oligomeric forms depending on the physicochemical characteristics of the solutions in which the experiments were performed. Remarkably, regardless of its oligomeric state, SfC12DO maintains its enzymatic activity even after prior lyophilization. All these characteristics make SfC12DO a putative candidate for bioremediation applications in polluted soils or waters.